2010
DOI: 10.3390/medicina46030026
|View full text |Cite
|
Sign up to set email alerts
|

Delusions of persecution and poisoning in patients with schizophrenia: sociocultural and religious background

Abstract: Summary. This article presents data on the phenomenology of delusions of persecution and poisoning in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
2
0
4
Order By: Relevance
“…appear stable, they demonstrate cultural plasticity in their content [3, 4]. For example, transcultural studies have identified universal delusional experiences amongst people with schizophrenia [5] with persecutory delusions being the most commonly reported across a diverse range of samples drawn from Austria [6]; China, Japan and South Korea [7]; India [8]; Lithuania [9]; Pakistan [10] Turkey [11] and the United States [12]. However socio-cultural factors such as religious belief systems [6, 13, 14] and more collective or individualistic conceptualizations of self [15] as well as environmental factors [16], historical events [12] and political contexts [7,9,] have been shown to influence the content of delusions.…”
Section: Introductionmentioning
confidence: 99%
“…appear stable, they demonstrate cultural plasticity in their content [3, 4]. For example, transcultural studies have identified universal delusional experiences amongst people with schizophrenia [5] with persecutory delusions being the most commonly reported across a diverse range of samples drawn from Austria [6]; China, Japan and South Korea [7]; India [8]; Lithuania [9]; Pakistan [10] Turkey [11] and the United States [12]. However socio-cultural factors such as religious belief systems [6, 13, 14] and more collective or individualistic conceptualizations of self [15] as well as environmental factors [16], historical events [12] and political contexts [7,9,] have been shown to influence the content of delusions.…”
Section: Introductionmentioning
confidence: 99%
“…Three major findings have emerged from previous studies: 1) the content and types of delusions and hallucinations differ among cultures8-12; 2) sociodemographic variables are associated with certain delusions and hallucinations13,14; 3) the content and frequency of delusions change over time within a given culture 15-17. Thus, the existing evidence consistently demonstrates that the delusions and hallucinations of schizophrenia reflect the societal status and cultural milieu of the patient.…”
Section: Introductionmentioning
confidence: 91%
“…In der Literatur lassen sich hierzu widersprüchliche Ergebnisse finden. Während Gecici et al ebenfalls berichten, dass innerhalb eines türkischstämmigen Patientenkollektivs Frauen mit einer Schizophrenie häufiger vom VW betroffen waren als an Schizophrenie erkrankte Männer [11], konnten Rudaleviciene et al in ihrer Untersuchung litauischer Patienten und Huber & Gross in ihrer Untersuchung deutschstämmiger Patienten keine derartigen Geschlechterunterschiede feststellen [14,16]. Darüber hinaus wiesen Frauen der hier beschriebenen Studie signifikant häufiger als Männer zusätzlich einen Beeinträchtigungs-und Verfolgungswahn auf.…”
Section: Auswertungunclassified
“…Das erhöhte Vorkommen von Beeinträchtigungs-und Verfolgungswahnvorstellungen bei Personen mit VW kann möglicherweise dahingehend erklärt werden, dass die beiden Wahnthemen so große Gemeinsamkeiten aufweisen, dass sie auch mit einer höheren Wahrscheinlichkeit zusammen auftreten. Auch Rudaleviciene et al berichteten in ihrer Untersuchung von einem starken Zusammenhang von VW und Verfolgungswahn [16]. Des Weiteren zeigt die zusammenfassende qualitative Inhaltsanalyse, dass Menschen mit VW häufig enge Angehörige oder das Gesundheitspersonal als vermeintliche Urheber der Vergiftung identifizieren.…”
Section: Auswertungunclassified
See 1 more Smart Citation